Experiences of mothers who are registrars in a department of anaesthesiology and the negotiations of their work-life balance - Bismilla, Nisaa (My University, 2021)
Background: The feminisation of medicine has resulted in a change in the demographic profile of the medical workforce. Female registrars are faced with gender-specific challenges of juggling multiple roles and responsibilities as mothers, professionals, students and spouses. The change in gender roles and constructs has led to concerns of work-life balance in female physicians. The aim of this study is to explore the experiences of work-life balance in registrar mothers and the assets with which they equip themselves in order to navigate the world of specialisation. Method: An exploratory, qualitative research design was employed in which in-depth, focused, open-ended one-on-one interviews were conducted with registrar mothers in the Department of Anaesthesiology at the University of the Witwatersrand between August 2019 and October 2019. Registrar mothers were asked about their experiences of work-life balance and how they negotiate these experiences. The interviews were audio recorded and transcribed verbatim and an inductive method of coding using Braun and Clark’s thematic analysis was applied. A hierarchical framework of data analysis was applied. Results; The rich data obtained from the interviews suggest that registrar mothers in the specialisation program experienced gender biases, maternal discrimination, high levels of stress, the perception of unequal opportunities for academic progression and work-life imbalance. Despite these challenges, these women make sense of their living world by constructing an identity with a multitude of dichotomous roles. This sense-making process allowed these registrar mothers to balance the stressors, work-life challenges and guilt they faced against the reward of professional excelling, and the multifaceted mother that they become as a result of personal fulfilment. They construct and rely on a strong support system from which they gain sustenance that enables them to succeed. Through this journey they mother themselves into becoming more than they imagined at the conception. Conclusion: This study demonstrates the complex, dynamic nature of juggling motherhood and professional development and the armamentarium employed by registrar mothers in order to negotiate the challenges they face. It demonstrates how registrar mothers make sense of their lived reality and the reconstruction of their ideological identity. Their process of sense-making and negotiation allows them to excel in multiple spheres of life
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology, 2021